Pengembangan Media Wayang Kartun Untuk Meningkatkan Keterampilan Menyimak Pada Tema 2 Subtema 1 Siswa Kelas III SDN 091407 Sarimatondang - Doharma Evita Mayasari Sidabutar; Erlinda Simanungkalit; Dody F Pandimun Ambarita; Faisal Faisal; Waliyul Waliyul (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to determine the feasibility, practicality and effectiveness of Cartoon Puppet Media to improve students' listening skills in Theme 2 Sub-theme 1 for Class III Students at SD N 091407 Sarimatondang. This research is research and development using the ADDIE development model which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. Based on the research results obtained, validation by media experts obtained 90% in the